1995
DOI: 10.1091/mbc.6.9.1173
|View full text |Cite
|
Sign up to set email alerts
|

Transient, lectin-like association of calreticulin with folding intermediates of cellular and viral glycoproteins.

Abstract: The soluble, calcium-binding protein calreticulin shares high sequence homology with calnexin, a transmembrane chaperone of glycoprotein folding. Our experiments demonstrated that calreticulin, like calnexin, associated transiently with numerous newly synthesized proteins in the endoplasmic reticulum. The population of proteins that bound to calreticulin was partially overlapping with those that bound to calnexin. Hemagglutinin (HA) of influenza virus was shown to associate with both calreticulin and calnexin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
216
0
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(223 citation statements)
references
References 57 publications
6
216
0
1
Order By: Relevance
“…The 70-kDa doublet from melanoma cells was, however, able to bind a bacterially produced, purified, recombinant glutathione S-transferasecalreticulin fusion protein in vitro (data not shown). The in vitro binding to calreticulin suggested that tyrosinase possessed the necessary monoglucosylated glycans required also for calreticulin binding in vivo (40) but that the microenvironment within the ER did not permit this association.…”
Section: Resultsmentioning
confidence: 98%
“…The 70-kDa doublet from melanoma cells was, however, able to bind a bacterially produced, purified, recombinant glutathione S-transferasecalreticulin fusion protein in vitro (data not shown). The in vitro binding to calreticulin suggested that tyrosinase possessed the necessary monoglucosylated glycans required also for calreticulin binding in vivo (40) but that the microenvironment within the ER did not permit this association.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, we asked if other ER proteins (both soluble and integral membrane proteins) were also able to escape from the ER and reach the cell surface. CRT is a multifunctional, peptide and Ca 2ϩ -binding molecular chaperone that is highly homologous to calnexin's lumenal domain (39,40). However, unlike calnexin, CRT is a soluble protein that is found in the ER lumen and that is retained by a distinct motif (KDEL) and a distinct retention receptor (KDEL receptor).…”
Section: Resultsmentioning
confidence: 99%
“…We propose that ERGIC-53 recognizes fully folded high-mannose glycoproteins in the ER after they have been released from the proposed quality control machinery for protein folding and N-glycan trimming consisting of the UDP-Glc:glycoprotein glucosyltransferase/calnexin/ER glucosidase cycle (Sousa et al, 1992;Sousa and Parodi, 1995;Hammond et al, 1994;Hebert et al, 1995;Peterson et al, 1995). COP I or COP II coats then bind to the cytoplasmic sorting signals of ERGIC-53 and drive the lectin-glycoprotein complex into budding vesicles.…”
Section: Hypothesis Of Ergic-53 Functionmentioning
confidence: 99%